(untitled) (Baghdad Science Journal, 2025)
This study aims to study the effect of gout disease on complete blood picture and biochemical parameters and some non-enzymatic antioxidants, some tracing elements and lipid peroxidation ,in outpatients with gout disease at Al-Ramadi Teaching-Hospital ,Al-Razi Hospital and the study duration from Octo.2013-to May 2014.(50) blood samples were collected from patients with age groups (30-80 years) from both sexes (28 males,22 females),a (30) blood samples (15 males,15 females) were collected from normal individuals as a control group with age groups (27-75 years). Hematological measurement showed no significant differences in size compressed blood cells, the percentages in ( 45.15 +4.99 and 46.87+6.30) % in patient and control groups respectively, hemoglobin concentrations were ( 14.04+1.66 and 14.30+1.93) g/l in patient and control groups respectively, total number of red blood cells ( 5.21+0.43 and 5.12 +0.58) 106/mm3 in patient and control groups respectively with(P?0.05) in ESR (21.06+13.47 and 13.37 +7.45) mm/hr in patient and control groups respectively with (P?0.05), the total number of WBCs were recorded (8.96+2.04 and 7.50+1.69)in patient and control groups respectively. Results showed also significant differences (P?0.05) in uric acid levels (7.42+0.76 and 5.62+0.88) mg/dl,malondialdehyde levels were recorded (4.45+0.64 and 3.21+0.86) in patient and control groups